Investigation of the Physicochemical Properties of the Active Compound in Clove Buds and Its Biological Activity Against Selected Bacterial Strains - Salih Hassan Ahmed Hassan (Journal of Scientific and Human Dimensions, 2026)
This study investigates the relationship between the physicochemical properties and chemical composition of the active compound in clove buds and its biological activity against selected bacterial strains. Clove extracts were prepared using different solvents (aqueous, ethanolic, methanolic, hexane) and analyzed for their physicochemical properties and chemical constituents. The antibacterial activity was tested against four standard Gram-positive and Gram-negative bacterial strains. Results showed significant variation in total phenolic and flavonoid content depending on the solvent, with alcoholic extracts outperforming aqueous and hexane extracts. The ethanolic extract demonstrated the highest antibacterial efficacy, exhibiting lower MIC and MBC values compared to other extracts. Statistical analysis revealed that certain physicochemical properties, such as solid content and viscosity, were significantly correlated with biological activity. These findings suggest that optimizing the type of solvent and extract characteristics can enhance clove’s antibacterial potential, supporting its application in medicinal and food industries.